2013
DOI: 10.18034/abcjar.v2i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Economic Globalization, Income Inequality and Economic Growth in Nigeria: A Static Data Analysis (1986-2010)

Abstract: This study examines the impact of economic globalization on income inequality and economic growth in Nigeria from 1986 to 2010. The study methodology was mainly Static Linear Econometric Model. Two models were used to test the two dependent variables simultaneously. The findings revealed that economic globalization had caused a widening income inequality as well as reduced economic growth of Nigerian economy due to much emphasis on financial globalization and other macroeconomic imbalances rather than trade gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…The findings of this study showed that trade globalisation and financial globalisation have differential or separate significant impacts on income inequality in Nigeria. Thus, trade globalisation is negatively associated with inequality in Nigeria, and this finding is in line with the findings by Lall et al (2007), Xu and Zou (2000) and Gries and Redlin (2009), while financial globalisation is positively associated with inequality and in line with the findings by Ogunyomi et al (2013). Furthermore, the study observes that economic growth (GRT) has negative and significant impact on income inequality, indicating that a unit increase in economic growth is expected to reduce inequality by 3.48 per cent in the long run.…”
Section: Ardl Estimatesupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study showed that trade globalisation and financial globalisation have differential or separate significant impacts on income inequality in Nigeria. Thus, trade globalisation is negatively associated with inequality in Nigeria, and this finding is in line with the findings by Lall et al (2007), Xu and Zou (2000) and Gries and Redlin (2009), while financial globalisation is positively associated with inequality and in line with the findings by Ogunyomi et al (2013). Furthermore, the study observes that economic growth (GRT) has negative and significant impact on income inequality, indicating that a unit increase in economic growth is expected to reduce inequality by 3.48 per cent in the long run.…”
Section: Ardl Estimatesupporting
confidence: 91%
“…The results also showed that in Southern Africa, access to secondary education and dependence on natural resources strongly and significantly reduce income inequality, while population growth and domestic investment rate have positive and significant impact on income inequality. Ogunyomi et al (2013) examined the effect of economic globalisation on economic growth and income inequality in Nigeria. The study covers the period of 1986-2010 and the ordinary least-squares technique was used.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Neo-liberalism economic policy that pushed globalization had contributed to raise the income inequality (Cornia and Kiiski, 2001). Pessimistically, globalization considered a thing that affected the increase of income inequality (Mahesh, 2016;Zakarian and Fida, 2016;Wong, 2016;Asteriou et al, 2014;Ogunyomi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%